TONGUE MICROFLORA AND PERIODONTAL DISEASE - Adriana Monea; Monica Monea; Diana Pop; Gabriela Beresescu (European Scientific Journal, ESJ, 2014)
Aim of the study. To determine the role of bacteria on the dorsal surface of the tongue in periodontal disease. Material and methods. Fifthytwo patients aged 18 to 25 were enrolled in the study; the subjects had to complete a questionnaire on general health, diet and dental hygiene habits. Decay-missing- filled teeth index (DMFT), the periodontal screening index (PSI), bleeding on probing (BOP) and plaque index were recorded for all subjects. After clinical examination, samples from dental plaque and tongue microflora were harvested by swabbing with sterile cotton sticks. Results. Clinical data obtained correlate with tongue microflora. The microflora does not depend on age and sex of the pacient. The counts of S.mutans was found to be corelated with DMFT index and also, the BOP with P.gingivalis (p=0.0006). We found the presence of P.gingivalis in approximately 12% of the subjects. Conclusions. The tongue surface can be an important reservoir for pathogens bacteria which can have a direct influence in the development of dental caries, oral halitosis or periodontitis.